Efficacy of fine needle aspiration cytology in the diagnosis of lymphadenopathies - Fatima, Rasheed; M., Sandhya (International Journal of Research in Medical Sciences, 2017)
Background: Enlarged lymph nodes were the first organs to be diagnosed by fine needle aspiration. Objectives were to study the role of FNAC in the evaluation of lymphadenopathies, to study the various cyto-morphological patterns in correlation with histopathology of various lymph node lesions and to document the diagnostic accuracy of FNAC in correlation with histopathology. Methods: All patients referred to the department of pathology K.V.G. Medical College and Hospital, Sullia, Karnataka, India for FNAC of palpable lymph nodes were included in present study. FNAC was done and the standard method for the procedure adopted. All the slides were reviewed and their diagnosis was made. FNAC diagnosis was compared with histopathology in cases which underwent surgical excision and thus its diagnostic accuracy determined. This was two years and two months’ prospective study from July 2008 to August 2010. Results: A total of` 150 patients were included in the present study, reported to various clinical departments with history of swelling. Lymph node biopsy was done in 50 cases. Statistical analysis was done in 50 cases, where FNAC diagnosis was correlated well with histopathological diagnosis. Maximum number of cases was in the age group of 31-40 years. Present study showed female preponderance of cases. Cervical group of nodes were most commonly involved. Benign lymphadenopathies were diagnosed in 69.8% of cases. Maximum number of cases being reactive lymphadenitis (65.4%). Metastatic deposit was diagnosed in 23.5% of cases. Most common subtype being adenocarcinoma. Lymphomas were diagnosed in 09 cases. 1 case of Hodgkin’s lymphoma and 8 cases of NHL were diagnosed. The overall correlation between FNAC and histopathology was 98% (49 out of 50). Conclusions: FNAC is an accurate, sensitive, specific and cost effective procedure in the diagnosis of lymphadenopathies.